Implementation of The Balanced Scorecard in Measuring The Performance of A Company - Fitria, Pipit (Ann Publisher, 2023)
This research aims to determine the company's performance at PT. Bank Rakyat Indonesia Syariah, Tbk. Which is used to measure and evaluate with the balanced scorecard method approach. This study uses the balanced scorecard method which evaluates in four important perspectives at PT. Bank Rakyat Indonesia Syariah, Tbk which includes a financial perspective, internal business process perspective, customer perspective, and growth and learning perspective from the 2019-2020 period.